2018
DOI: 10.1177/0300060517738426
|View full text |Cite
|
Sign up to set email alerts
|

Among middle-aged adults, snoring predicted hypertension independently of sleep apnoea

Abstract: ObjectiveWhile the link between obstructive sleep apnoea (OSA) and hypertension is well established, the relationships between snoring, OSA, and hypertension remain unclear. This study aimed to evaluate the association between hypertension and snoring independently of OSA.MethodsAdults with sleep difficulties underwent a one-night polysomnographic sleep assessment, including a thorough assessment of apnoea and snoring. Upon waking, blood pressure was measured, the measurement repeated after 15 min, in a restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Participants between 12 and 40 years from Kermanshah City (Kermanshah, Iran) and self-reporting issues with gaming were invited to participate in this cross-sectional study on game addiction. The age range spans the developmental period of early adolescence ( 26 ) to the end of young adulthood ( 27 , 28 ). Those eligible for participation were fully informed about the aim of the study and the anonymous data handling, and signed a written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Participants between 12 and 40 years from Kermanshah City (Kermanshah, Iran) and self-reporting issues with gaming were invited to participate in this cross-sectional study on game addiction. The age range spans the developmental period of early adolescence ( 26 ) to the end of young adulthood ( 27 , 28 ). Those eligible for participation were fully informed about the aim of the study and the anonymous data handling, and signed a written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The most important epidemiological risk factors for OSAS are obesity and male gender ( 9 , 10 ). OSAS plays an important role in the emergence and maintenance of hypertension, while snoring is a risk factor for hypertension independent of body mass index (BMI), AHI, or older age ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sixth, one study reported that among middle-aged people, snoring and not OSA predicted hypertension, but the records of snoring were not included in the NHIRD. 68 Finally, the NHI program started in 1995, but in this study, the NHIRD we used contained a database of 15 years only. We highly recommend that a longer follow-up study is needed in the future.…”
Section: Limitations Of This Studymentioning
confidence: 99%